Inside a Secret Software Laboratory An Ethnographic Study of a Global Software Package Producer - Grimm, Christine; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
How does one of the world$1 (Bs biggest Enterprise Resource Planning (ERP) suppliers develop software? How do Oracle, SAP, Microsoft and Co really work? Christine Grimm presents a first-hand account of a social researcher who entered the software laboratory of one of the biggest ERP providers. Presenting an in-depth ethnography on how people act within such labs, she reveals the highly unexpected social character of programming and shows how the vendor reorganizes himself to find new ways to respond to the expectations of the market. Furthermore, the author highlights the informal practices when an ERP system, as a defective or incomplete product, re-enters the supplier$1 (Bs labs. The book provides a window into what happens if bugs are dug up and emotions on both the supplier and customer sides are running high.s
Keywords: Economics; Economics/Management Science; Business/Management Science, general